2013
DOI: 10.7763/ijmlc.2013.v3.297
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Artificial Neural Networks via Instance Selection and Feature Dimensionality Reduction

Abstract: Abstract-This paper presents a hybrid approach with two phases for improving the performance of training artificial neural networks (ANNs) by selection of the most important instances for training, and then reduction the dimensionality of features. The ANNs which are applied in this paper for validation, are included Multi-Layer Perceptron (MLP) and Neuro-Fuzzy Network (NFN). In the first phase, the Modified Fast Condensed Nearest Neighbor (MFCNN) algorithm is used to construct the subset with instances very c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…An exhaustive search strategy can generate the best solution. [13][14][15][16] However, evaluation of all possible subsets is impractical even for small-size circuits, due to computational complexity. 16 It has been shown that swarm intelligence algorithms (e.g., GA, particle swarm optimization, ant colony optimization, etc.)…”
Section: Traditional Simpli¯cation Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…An exhaustive search strategy can generate the best solution. [13][14][15][16] However, evaluation of all possible subsets is impractical even for small-size circuits, due to computational complexity. 16 It has been shown that swarm intelligence algorithms (e.g., GA, particle swarm optimization, ant colony optimization, etc.)…”
Section: Traditional Simpli¯cation Criteriamentioning
confidence: 99%
“…can e±ciently be applied for NP-hard problems. [13][14][15][16] Therefore, GA is used for the simpli¯cation of analog circuits in this paper in order to achieve the best performance.…”
Section: Traditional Simpli¯cation Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Using all the aforementioned attributes may not result in the most accurate CAD system because there may be some irrelevant or noisy attributes that hinder the system's ability to distinguish between healthy and cancer patients correctly. Therefore, it is crucial to adopt an appropriate attribute selection strategy in order to select the most important subset of attributes that can be later used to classify patients accurately (Abroudi et al, 2013). Numerous CAD systems for early detection of breast cancer have been presented and they have used different data as well as different metrics to measure the system classification performance (Table 1).…”
Section: Introductionmentioning
confidence: 99%